Transient Left Bundle Branch Block During the Recovery Period of a Stress Test - Efrat Mazor Dray; Yuval Konstantino; Reuben Ilia (Journal of Hypertension and Cardiology, 2014)
Exercise-dependent complete left bundle branch block is a rare entity.We present a case in which this phenomenon was demonstrated during the recovery period of a stress test. To the best of our knowledge such an observation has not been previously described.
Keywords: Left Bundle Branch Block